Protection by Lactobacillus acidophilus UFV-H2B20 against experimental oral infection with Salmonella enterica subsp. enterica Ser. Typhimurium in gnotobiotic and conventional mice - Moura,Lilian Nobre (2001)
The ability of Lactobacillus acidophilus UFV-H2B20 to antagonize Salmonella enterica subsp. enterica ser. Typhimurium and to reduce the pathological consequences for the host was determining using conventional and gnotobiotic animals. Conventional NIH mice received daily by gavage a 0.1 ml suspension containing about 10(8) cfu L. acidophilus UFV-H2B20 and germfree animals received a single 0.1 ml dose. The gnotobiotic and conventional groups were infected orally with 10² and 10(5) cfu of S. Typhimurium, respectively, 7 days after the beginning of treatment. Control groups were treated with sterile saline instead of Lactobacillus. Survival data showed a protective effect against the pathogenic bacteria in both conventional and gnotobiotic Lactobacillus-treated mice. L. acidophilus UFV-H2B20 colonized the digestive tract of gnotobiotic mice and the number of viable cells ranged from 10(9) to 10(10) cfu/g of faeces. In both experimental and control gnotobiotic animals, S. Typhimurium became rapidly established at a level ranging from 10(8) to 10(10) cfu/g of faeces and remained at high levels until the animals died or were sacrificed. In conclusion, the previous treatment of mice with L. acidophilus UFV-H2B20 protects the animals against the experimental infection with S. Typhimurium but this protection was not due to the reduction of the pathogenic populations in the intestines.